Peningkatan Literasi Digital Dasar Melalui Pembuatan Akun Email dan Pemanfaatan Taman Belajar bagi Siswa SMPN SATAP 1 Riung di Desa Lengkosambi Kecamatan Riung: Improving Basic Digital Literacy Through Creating Email Accounts and Utilizing Learning Parks for Students of SMPN SATAP 1 Riung in Lengkosambi Village, Riung District - Simo, Daniel; Noywuli, Nicolaus; Setiono, Devit (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Digital literacy is an essential competency in the modern era, yet it remains a challenge in remote areas. This service activity aims to improve the basic digital literacy of SMPN Satap 1 Riung students by focusing on two main areas: creating an email account and using the Learning Park as a learning medium. The method used is participatory training and mentoring. The results showed that students were able to create and manage email accounts independently and use basic internet features to support learning, such as searching for information and sending assignments. The evaluation showed an increase in students’ digital understanding and skills, which were previously very limited. These activities not only improve technical skills, but also foster awareness of the importance of digital literacy for their future.